Evaluating training effectiveness focus on the training of public enterprise managers - Iglesias, Gabriel U. (Philippine Journal of Public Administration, 1982)
Evaluation of training effectiveness is generally accepted as important in measuring levels or changes in individual, unit and organizational performance. A comparison of the experience of selected developed and developing countries, however, show that there has been relative neglect, on the part of the latter, to use more rigorous and reliable evaluation instruments, techniques, and methodologies in measuring the effectiveness of training conducted on public enterprise managers. There is need therefore to strengthen the capability of training institutions in evaluating training effectiveness.